Development of a Novel Virus-Like Particle-Based Vaccine Against PRV-1 Suitable for DIVA Strategies - Vasquez-Martinez, y (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Piscine orthoreovirus genotype 1 (PRV-1) is an emerging viral pathogen in salmon aquaculture that causes Heart and Skeletal Muscle Inflammation (HSMI), with high prevalence in salmon-producing countries such as Chile. A significant obstacle in PRV-1 vaccine development is the inability to culture the virus in vitro, which limits the scalability and production of traditional inactivated or DNA-based vaccine strategies. This study describes the development of a novel virus-like particle (VLP)-based vaccine against PRV-1. Recombinant VLP were produced by co-expressing the six structural proteins of PRV-1 (λ1, λ2, μ1, σ1, σ2, σ3) using a baculovirus-based expression system in insect cells. In addition, to enable differentiating infected from vaccinated animals (DIVA) strategies, the σ1 protein was modified by adding of a cmyc epitope tag. The results demonstrated that the native VLP vaccine (VLP6n) significantly reduced viral loads in Atlantic salmon challenged with PRV-1. Moreover, in rainbow trout, the cmyc-tagged VLP-like vaccine (VLP6c) elicited a specific antibody response against the cmyc epitope, allowing differentiation between vaccinated and naturally infected fish. Overall, this VLP-based vaccine platform represents a promising strategy for controlling PRV-1 prevalence in salmon-producing counties, supporting the implementation of serological surveillance programs. © 2025 by the authors.